Ҳ.ӨТЕМУРАТОВА ГҮРРИҢЛЕРИНДЕ КӨРКЕМ ШЕБЕРЛИК - Ктайбекова, З.К. (SCIENCE and SOCIETY, 2021)
The article describes the artistic features of H. Utemuratova’s stories. In particular, one thinks about the writer’s skill in creating characters, heroes, images. The issue of conflict in the works, the problems of life are revealed through a series of events. The stories depict the breath of the independence era, new images, new thinking and the expression of heroes with unexpected twists and turns. ЎЗБЕК ФОЛЬКЛОРИДА ЛОФ ВА ЭРТАК ЖАНРЛАРИНИНГ МУНОСАБАТИ Д.Мехлиева – таянч докторант ЎзРФА Ўзбек тили, адабиѐти ва фольклори институти Таянч сўзлар: лоф, лофчи, ҳажвий эртак, муболаға, кал. Ключевые слова: лоф, лофчи, комикс, преувеличение, кал. Key words: Lof, lofchi, comic tale, exaggeration, kal. Халқ оғзаки ижодининг бугун биз ―жанр‖ деб атайдиган намуналари қачон пайдо бўлгани номаълум